Beryllium Dimer Reactions with Acetonitrile: Formation of Strong Be−Be Bonds - Fei Cong; Liyan Cai; Juanjuan Cheng; Zhen Pu; Xuefeng Wang (Molecules, 2023)
Laser ablated Be atoms have been reacted with acetonitrile molecules in 4 K solid neon matrix. The diberyllium products BeBeNCCH3 and CNBeBeCH3 have been identified by D and 13C isotopic substitutions and quantum chemical calculations. The stabilization of the diberyllium species is rationalized from the formation of the real Be−Be single bonds with bond distances as 2.077 and 2.058 Å and binding energies as −27.1 and −77.2 kcal/mol calculated at CCSD (T)/aug-cc-pVTZ level of theory for BeBeNCCH3 and CNBeBeCH3, respectively. EDA-NOCV analysis described the interaction between Be2 and NC···CH3 fragments as Lewis “acid−base” interactions. In the complexes, the Be2 moiety carries positive charges which transfer from antibonding orbital of Be2 to the bonding fragments significantly strengthen the Be−Be bonds that are corroborated by AIM, LOL and NBO analyses. In addition, mono beryllium products BeNCCH3, CNBeCH3, HBeCH2CN and HBeNCCH2 have also been observed in our experiments.